Ultimate illustrated guide to sewing clothes : a complete course on making clothing for fit and fashion - Mahon, Joi (Landauer Publishing, 2022)
"A comprehensive manual on everything you need to know on how to sew clothes! The Ultimate Illustrated Guide to Sewing Clothes is a must-have resource filled with valuable insight on sewing, tailoring, making alterations, and more. Learn how to take a pattern you already have and adjust it to your unique needs, install a zipper, use notions, and get a good fit out of any sewing pattern for any body type! Whether you're new to sewing or have experience, expand your skill set and build confidence so you can sew like a pro! Also included is a bonus tutorial on making pants and fitting material, as well as finishing your garments and instructions on detailing to make one-of-a-kind clothes"--